Epstein-Barr virus nuclear antigen 3C (EBNA3C) interacts with the metabolism sensing C-terminal binding protein (CtBP) repressor to upregulate host genes. - Makoto Ohashi; Mitchell Hayes; Kyle McChesney; Eric Johannsen (PLoS Pathogens)
Epstein-Barr virus (EBV) infection is associated with the development of specific types of lymphoma and some epithelial cancers. EBV infection of resting B-lymphocytes in vitro drives them to proliferate as lymphoblastoid cell lines (LCLs) and serves as a model for studying EBV lymphomagenesis. EBV nuclear antigen 3C (EBNA3C) is one of the genes required for LCL growth and previous work has suggested that suppression of the CDKN2A encoded tumor suppressor p16INK4A and possibly p14ARF is central to EBNA3C's role in this growth transformation. To directly assess whether loss of p16 and/or p14 was sufficient to explain EBNA3C growth effects, we used CRISPR/Cas9 to disrupt specific CDKN2A exons in EBV transformed LCLs. Disruption of p16 specific exon 1α and the p16/p14 shared exon 2 were each sufficient to restore growth in the absence of EBNA3C. Using EBNA3C conditional LCLs knocked out for either exon 1α or 2, we identified EBNA3C induced and repressed genes. By trans-complementing with EBNA3C mutants, we determined specific genes that require EBNA3C interaction with RBPJ or CtBP for their regulation. Unexpectedly, interaction with the CtBP repressor was required not only for repression, but also for EBNA3C induction of many host genes. Contrary to previously proposed models, we found that EBNA3C does not recruit CtBP to the promoters of these genes. Instead, our results suggest that CtBP is bound to these promoters in the absence of EBNA3C and that EBNA3C interaction with CtBP interferes with the repressive function of CtBP, leading to EBNA3C mediated upregulation.